Small Ruminants Marketing in Ethiopia and the Need to Rethink - Legese, Getachew (International Center for Agricultural Research in the Dry Areas, 2022)
Small Ruminants Marking in Ethiopia and the Need to Rethink presentation at the 30th ESAP Annual Conference. Hawassa, Ethiopia. September 16th, 2022.